The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1590/s0100-41582005000200015
|View full text |Cite
|
Sign up to set email alerts
|

Germinação e penetração de Stenocarpella macrospora em folhas de milho

Abstract: O sucesso do estabelecimento de uma relação parasitária entre fungos e plantas, em muitos casos, depende de eventos que antecedem à infecção. Neste trabalho, as fases compreendidas entre a germinação e a penetração do fungo Stenocarpella macrospora foram analisadas por meio de microscópio eletrônico de varredura. Para tanto, plantas de milho (Zea mays) híbrido Das-8492, suscetível à mancha foliar de diplodia, foram cultivadas em casa de vegetação e inoculadas com 300 µl de uma suspensão de 10(5) conídios/ml ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…However, for leaves treated with India clove oil, appressorium formation occurred at 25h after inoculation. In the same way, BRUNELLI et al (2005) conducted SEM analysis and found that 86% of the conidia of Stenocarpella macrospora germinated between 12 and 15h after inoculation and appressorium formation occurred at 18h.a.i. Furthermore, oils from India clove and thyme caused wilting of some conidia at 30h.a.i.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for leaves treated with India clove oil, appressorium formation occurred at 25h after inoculation. In the same way, BRUNELLI et al (2005) conducted SEM analysis and found that 86% of the conidia of Stenocarpella macrospora germinated between 12 and 15h after inoculation and appressorium formation occurred at 18h.a.i. Furthermore, oils from India clove and thyme caused wilting of some conidia at 30h.a.i.…”
Section: Discussionmentioning
confidence: 99%
“…The parasitic relationship between S. maydis and maize leaves may be well understood using the Scanning electron microscope (SEM) analysis, which is a valuable tool to study adhesion, germination, penetration, colonization, and reproduction of pathogens (ALVES et al, 2008). In this way, BRUNELLI et al (2005) and MEDICE el at. (2007) verifi ed that the essential oils act on the conidia germination and on the appessorium formation as well.…”
Section: Introductionmentioning
confidence: 97%
“…The field fungi require high humidity to grow, as the Stenocerpella complex, Diplodia complex scientific name, consisted of two species, Stenocarpella maydis (Berk.) Sutton, and Stenocarpella macrospora (Earle) Sutton (Brunelli et al, 2005). Currently, the two Stenocarpella species can be detected in all corn producing areas in the country, causing symptoms of diplodia stalk rot, white ear rot and macrospora stain on leaves (Casa et al, 2006).…”
Section: Introductionmentioning
confidence: 99%